2004
DOI: 10.1177/039463200401700309
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Microdomains Mediate CD38 Internalization: Topography of the Endocytosis

Abstract: Plasma membranes of several cell types contain specialized microdomains (or lipid rafts) enriched in sphingolipids, cholesterol, sphingomyelin, and glycosyl-phosphatidylinositol-anchored proteins. These membrane domains are characterized by detergent insolubility at low temperatures and low buoyant density. Human CD38 is the prototype of a gene family encoding surface molecules endowed with multiple functional activities. The endocytosis of the human CD38 molecule has been investigated in normal lymphocytes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…These lipid platforms may recruit or aggregate various signaling molecules such as trimeric G proteins, small G proteins, sphingomyelin (SM), tyrosine kinases, NADPH oxidase subunits, phosphatases, and many others, resulting in the activation of different signaling pathways. Recent studies have reported that LRs are closely associated with the CD38 pathway in various lymphocytes and these LRs may be responsible for endocytosis of CD38 and the activation of certain signaling pathways (35,46). However, the identity of these LRs remains unclear, and it is also unknown whether LRs during its clustering are involved in cADPRmediated Ca 2ϩ signaling.…”
mentioning
confidence: 99%
“…These lipid platforms may recruit or aggregate various signaling molecules such as trimeric G proteins, small G proteins, sphingomyelin (SM), tyrosine kinases, NADPH oxidase subunits, phosphatases, and many others, resulting in the activation of different signaling pathways. Recent studies have reported that LRs are closely associated with the CD38 pathway in various lymphocytes and these LRs may be responsible for endocytosis of CD38 and the activation of certain signaling pathways (35,46). However, the identity of these LRs remains unclear, and it is also unknown whether LRs during its clustering are involved in cADPRmediated Ca 2ϩ signaling.…”
mentioning
confidence: 99%
“…PMA treatment on K562 cells, on the contrary, did not lead to any increase of fluorescence, despite the induced-CD38 expression on their cell membrane. We have already proved that internalization never involves the entire amount of surface molecules, indicating the presence of two distinct pools of CD38 [5,6]. In other works, we have, moreover, demonstrated that CD38 on the surface of treated K562 cells is an active enzyme with cyclase activity [14].…”
Section: Discussionmentioning
confidence: 57%
“…However, there is no evidence that these two subsets of CD38 perform different enzymatic tasks. In previous studies, we have shown that CD38 endocytosis is preceded by extensive rearrangement of the cell surface, with the formation of glycosphingolipid-rich and cholesterol-rich plasma membrane microdomains [6]. Receptor-mediated endocytosis is essential for monoclonal antibody (mAb) therapy, as it allows the conjugation of toxins to be internalized only by target cells.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that NOX1 and CD38 tends to colocalize in special plasma MR domains upon ET-1 stimulation and such spatial organization supports the view that NOX1-derived O 2 · − interacts with CD38 in such MR domains, which may oxidize the cysteine residues of CD38 leading to its internalization and activation. Recent studies have reported that MRs are closely associated with the CD38 pathway in various lymphocytes and that these MRs may be responsible for the endocytosis of CD38 [34], [51], [52]. Our previous studies also showed that ceramide-enriched lipid macrodomains contribute to CD38 activity to produce cADPR in CAMs [34] and that MRs platforms mediate the aggregation of membrane NADPH oxidase subunits and subsequent activation of this enzyme in bovine coronary arterial endothelial cells [53].…”
Section: Discussionmentioning
confidence: 88%